El rol de pago, provisión de beneficios y prestaciones laborales en la empresa la Oferta Cía. Ltda. año 2018. - Gonzales Marquez, Evelin Brigitte (My University, 2018)
In the development of this document we proceeded to review the procedures that correspond to the elaboration of the payment roles and the provision of benefits and work benefits in Ecuador, the objective is to be able to publicize the entire elaboration process, legal regulations and the generalities of the payment role. Faced with the constant failure and evasion of the employer to grant the employee the rights corresponding to their role as a worker, it has been considered convenient to carry out a complete review of what the payment roles are, their objectives, and their regulations, in order that both the remuneration and the benefits and provisions that by law correspond to reach the time and amount stipulated in the procedures. To get to establish such procedures, the study will be carried out in the company THE OFFER Cía. Ltda. From Ecuador, through a theoretical, accounting and legal approach, which will allow to establish the correct and correct way the income and deductions of the workers, giving way to an accounting practice with the legal estimate of all the concepts that make up the item remunerations.
En el desarrollo de este documento se procedió a revisar los procedimientos que corresponden a la elaboración de los roles de pago y la provisión de beneficios y prestaciones laborales en el Ecuador, el objetivo es poder dar a conocer todo el proceso de elaboración, normativa legal y las generalidades del rol de pago. Ante el constante incumplimiento y las evasiones del empleador por otorgar a el empleado los derechos correspondientes a su función de trabajador se ha creído conveniente llevar a cabo una completa revisión de lo que son los roles de pago, sus objetivos, y su normativa, a fin de que tanto la remuneración como las prestaciones y provisiones que por ley le corresponde lleguen el tiempo y la cuantía que se estipula en los procedimientos. Para llegar a establecer tales procedimientos, el estudio se realizará en la empresa LA OFERTA Cía. Ltda. Del Ecuador, a través de un enfoque teórico, contable y jurídico, que va a permitir establecer la manera adecuada y correcta los ingresos y deducciones de los trabajadores, dando paso a una práctica contable con la se estimen legalmente todos los conceptos que integran el rubro remuneraciones.
Keywords: ROL DE PAGO; BENEFICIOS; PRESTACIONES; PROCEDIMIENTOS; NORMATIVAS